The rise of social ereading : interactive ebook platforms and the development of online reading communities : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University, Manawatū, New Zealand - Pawley, Jessica Leigh (Massey University, 2016)
Ebooks have caused a revolution in how people read fiction. Ereading devices and apps now integrate interactive features which have led to the development of digital reading communities populated by millions of readers from around the world, with a resurgence of social reading practices in new forms. Two of the biggest social reading communities in existence today are hosted by Amazon’s Kindle and Wattpad. This thesis offers an analysis of how these platforms’ readers are using the interactive technology within the pages of their ebooks to participate in these online reading communities. Original research into popular texts on Wattpad reveals that while only a small percentage of users are actively engaging with the ebooks and other readers during the process of reading, all active and passive interactions have a significant influence on the reading experience. Thus, the infrastructure of such communities ‘rewards’ serialised books which encourage higher levels of reader interactivity with greater recognition within the community, but this reward is short-lived. The application of Genette’s paratextual theory to the interactive features of these ereading platforms reveals new processes of authorisation and readers-as-writers. New paths for the evolution of digital paratextual theory see paratexts developing from ‘thresholds’ into ‘vectors’. The statistical notations of reader interactions are now informational paratexts attached to each ebook, and these online reading communities may be considered paratexts themselves, operating through the new paratextual phenomenon of digital marginalia. Furthermore, the existence of these reading communities on free platforms such as Wattpad is supported by commercial paratexts found within the ebook pages. These new paratexts are having a significant impact on social ereading and reading communities - such as how they operate and judge the 'value’ of ebooks - but historical precedents suggest these paratexts will be readily accepted by most readers, leading to an increase in the incidence and influence of such digital paratexts. These new interactive technologies and paratexts will potentially lead to significant changes in how fiction is read. Exactly how these technologies may develop, and how public, industrial, and academic stakeholders might take advantage of these opportunities, requires further research.
Keywords: Electronic books; Social aspects; Books and reading; Technological innovations; Online social networks